Inflation expectations: Review and evidence - M. Ayhan Kose; Hideaki Matsuoka; Ugo Panizza; Dana Vorisek (Koç University-TÜSİAD Economic Research Forum (ERF), 2019)
This paper presents a comprehensive examination of the determination and evolution of inflation expectations, with a focus on emerging market and developing economies (EMDEs). The results suggest that long-term inflation expectations in EMDEs are not as well anchored as those in advanced economies, despite notable improvements over the past two decades. Indeed, in EMDEs, long-term inflation expectations are more sensitive to both domestic and global inflation shocks. However, EMDEs tend to be more successful in anchoring inflation expectations in the presence of an inflation targeting regime, high central bank transparency, strong trade integration, and a low level of public debt.
Keywords: E31; E37; E40; E50; 330; inflation; inflation expectations; monetary policy; emerging markets; developing economies